Minimum Wage Companies in the Second Wave of the Corona Crisis - Christian Kagerl; Clemens Ohlert (Wirtschaftsdienst)
Abstract For a number of reasons, businesses affected by minimum wage may have a particularly hard time during the coronavirus pandemic. We have found that minimum wage establishments were more frequently affected by the Corona pandemic than the rest of the economy at the beginning of 2021 due to the industry composition of these establishments rather than to minimum wage itself. The findings also indicate that minimum-wage establishments use short-time work more often and that the volume of work is reduced more frequently than in other establishments by cutting back on overtime. Finally, salary increases and special payments are also reduced or suspended more frequently.